Pengaruh Penggunaan Model Pembelajaran Project Based Learning Terhadap Kemampuan Kognitif Pemecahan Masalah Pada Anak Usia Dini - Zami, Ilma Madya Khoiri Zam; Ruhiat, Dadang; Nugraha, Anggi Purwa (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2024)
This study aims to examine the impact of the Problem Based Learning (PBL) model on problem-solving abilities in early childhood, specifically for children aged 4-5 years. The research employed a quantitative method with a Pre-Experimental approach. Observation and documentation were used to collect data from 13 children at PAUD Kasih Ibu, Sindangrasa Village, Ciamis Regency. The results showed that 85% of the children were able to solve problems at an